Scalable and efficient mobile authentication scheme preserving user privacy. (1st March 2013) - Pu, Qiong; Wang, Jian; Wu, Shuhua
User privacy is a notable security issue in wireless communications support roaming. However, the mobile authentication schemes existing in the literature cannot achieve this goal in an efficient way. In this paper, we propose a novel lightweight authentication scheme with anonymity and unlinkability for roaming service in large–scale wireless networks. Moreover, we formally analyse our proposed scheme with the BAN–logic and show that it can withstand the several possible attacks.